Effect of humic supplementation on the germination rate and some morphological characters of three cultivars of sorghum under salt stress conditions - Al-Taha, Ghada Mohammed Rashid (Journal of agricultural, environmental and veterinary sciences, 2024)
This research was carried out in the village of Hawija Al-Sawafi, (3 km south of Al-Raqqa Governorate), during the two growing seasons 2010 - 2011. In order to study the effect of humic addition on some growth and productivity characteristics of three cultivars of Sorghum under salt stress conditions. The experiment was designed using split plot design with three replications. The experiment included three different levels of salinity, (1.3, 7.6, and 10dm/m-1 respectively) and three levels of Humic acid (0, 1, 2 gl-1), and three varieties of sorghum. (Hammoui, Zuri and Azraa3). Where salinity levels represented the main plots, while the cultivars represented the splinter plots. While the humic applications were distributed in the subcutaneous splinter. The following characteristics were studied germination rate, number of tillers per plant, plant height, protein content of seeds. The results of the research showed a significant decrease in the average of the studied traits with the increase in soil salinity from (1.3 dmm-1) to (10 dmm-1). All cultivars were affected by the increase in salinity, and the Hamwi model was superior in the percentage of germination Germination rate and plant height, The addition of humic organic fertilizer at two concentrations 2 gl-1 of humic acid reduced the harmful effect of salinity on all studied traits. And the concentration exceeded 2 gl-1, gave the highest means for all the studied traits. The interaction between irrigation water salinity and humic acid application gave a significant result in the studied traits.